Urgensi Pengaturan Financial Technology: Kewenangan Penghimpunan Dana Masyarakat: The Urgency of Financial Technology Regulation: Authority to Collect Public Funds - Kurniawan, Wishnu; Birahayu, Dita (Faculty of Law Hang Tuah University, 2025)
Technological developments are driving acceleration in all fields, especially financial technology, where the services required for banking products are equivalent to those of banks. In line with current conditions, namely the advent of digital 4.0, financial institutions are beginning to shift to technology-based financial institutions. One of the current advancements in the financial sector is the adaptation of Financial Technology, commonly known as fintech. The implementation of fintech must not be hindered by legal violations due to legal loopholes. This study employs a normative legal approach. Based on this method, a statute approach is used in this study, reinforced by a literature approach. This study was conducted to accelerate the implementation of fintech so that it does not fall into a legal vacuum, thereby preventing problems arising from violations of norms, particularly in the banking sector. The modernity of financial transactions, especially financial services such as fintech, has violated the provisions of the Banking Law, which in this case is the establishment of business entities that attract public funds in banking institutions. However, to date, there is still a legal vacuum, and with the rapid development of technology, there needs to be a change in regulations related to this issue to prevent a legal vacuum.